Use of psylocybin in the treatment of psychiatric disorders: Literature review (Research, Society and Development, 2024)
Objective: To describe the information available in the literature regarding the use of psilocybin in the treatment of psychiatric disorders, its mechanisms of action and toxicity, as well as other relevant data on the subject. Methodology: This paper presents a narrative review of the literature, which allows for the synthesis of multiple studies, thus enabling general conclusions about a particular subject. The searches took place between the months of September and December of 2023, in the following databases: PubMed, Virtual Health Library, SciELO and Google Scholar. The critical analysis of the studies and the synthesis of bibliographic data were performed descriptively, grouped in topics relevant to the studied subject. Results: Given its mechanism of action – psilocybin acts mainly as an agonist of the 5-receptorHT2A, acting in the serotonergic system, amplifying the action of serotonin in the synaptic cleft and promoting qualitative and quantitative changes in brain function –, several studies relate psilocybin to the improvement of symptoms of depression and anxiety. As for the evaluation of the toxicity of this substance, psilocybin is generally considered of low-toxicity, not generating physical dependence. Conclusion: Considering the above, there is potential for this hallucinogen in the treatment of psychiatric disorders, such as depression and anxiety. However, more studies are still needed to better understand the efficacy of psilocybin, its risks and benefits, as well as to verify regulatory aspects and protocols for its safe and rational use.